The PQ4R Learning Model (Preview, Question, Read, Reflect, Recite, Review): Measuring Its Effectiveness on Students’ Learning Outcomes - Hasanah, Melati Nur Aini; Ruswanto, Ruswanto; Azizah, Nurul; Sada, Heru Juabdin; Yusnita, Erni (Journal of Educational Sciences, 2025)
This study aims to examine the effect of the PQ4R learning model on students’ learning outcomes at the cognitive levels of analysis (C4) and evaluation (C5). Employing a quantitative approach with a quasi-experimental posttest-only control group design, Samples were selected through simple random sampling. Class VIII.1 was assigned as the experimental group receiving the PQ4R learning model, while class VIII.7 served as the control group with conventional instruction. The research instrument was a 15-item multiple-choice test validated for validity and reliability. Data analysis began with assumption testing for normality and homogeneity. Levene’s test indicated an F-value of 1.184 with a significance of 0.281, confirming homogeneity of variance between groups. The hypothesis was tested using an independent samples t-test, yielding a t-value of 5.343 with 59 degrees of freedom and a significance level of 0.001 (p < 0.05), indicating a statistically significant difference between the groups’ mean scores. The mean difference of 1.62366 with a 95% confidence interval ranging from 1.01309 to 2.23168 further supports this result. These findings conclude that the PQ4R learning model significantly improves students’ analytical and evaluative thinking skills. Therefore, the PQ4R model is recommended as an effective instructional strategy for enhancing higher-order cognitive learning outcomes.